Grateful Personality in The Development of Islamic Education (Hermeneutical Analysis of Verses About Gratitude in Tafsīr Al-Miṣbāḥ) - Afandi, Nur Kholik (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to find out how the concept of personality gratitude in the development of Islamic education is described in the Quran. This research is included in the type of library research that uses qualitative data types. e main data source in this research is the Koranic verses that discuss gratitude. This study uses a subjective hermeneutic approach that emphasizes the interpreter's role in understanding and determining the meaning of the text about the verses of gratitude in Tafsr al-Misbah. According to the findings of the study, a grateful personality is synonymous with the term 'abdan syakuran. The term refers to a personality that always appreciates, recognizes, and uses God's grace in every situation. A person with a grateful personality has a noble character, which contains the character values of trustworthiness, qan'ah, tawadu', hard work, creativity, and prosocial actions. A grateful personality is needed to realize Islamic education's goals, namely the creation of religious and noble human beings. Therefore, we need the right strategy for instilling these values. The internalization of the gratitude personality in Islamic education can be carried out through several strategies, including tazkiyah, tazniyah, tadabburah, and tarabbutah.